2018
DOI: 10.1108/ijshe-09-2017-0152
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and engagement: strange bedfellows in the undergraduate textbook

Abstract: Purpose This paper aims to examine the textual coverage of the topic of public engagement in leading English language sustainability textbooks. Design/methodology/approach In this paper, the authors’ findings are based on a content analysis of 12 textbooks published between 2005 and 2015. The authors generated the sample through three sources: a review of the offerings of five major academic publishers, title searches of academic databases and an examination of the syllabi compiled by AASHE. Texts that displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In short, it can be concluded that, with such a high proportion of activities at a low cognitive level and mainly focused on aspects, such as environmental problems and recycling, textbooks might be insufficient for a broad treatment of sustainability. This is in line with the reports of other authors [35][36][37][38][39]. Therefore, the work of the teacher is fundamental to make up for possible deficiencies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In short, it can be concluded that, with such a high proportion of activities at a low cognitive level and mainly focused on aspects, such as environmental problems and recycling, textbooks might be insufficient for a broad treatment of sustainability. This is in line with the reports of other authors [35][36][37][38][39]. Therefore, the work of the teacher is fundamental to make up for possible deficiencies.…”
Section: Discussionsupporting
confidence: 86%
“…Several researches analyse the treatment given to sustainability by textbooks from different perspectives. Thus, some studies, such as that of Larkins et al [35], analyse several United States (US) textbooks that were published between 2005 and 2015, reporting the little attention paid to the ways in which people, groups, or institutions can participate in the pursuit of a sustainable society as a general idea. On the other hand, Muthukrishnan and Kelley [36] analyse the representations of sustainability in a set of books for children that can be acquired through Amazon, concluding the insufficiency of these books to describe sustainability, representing eco-sustainable practices only in post-consumption scenarios, without describing the effects of consumerism, such as the depletion of natural resources or pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The first peak occurred in 1996, the book “Education for Sustainability” [10] (Huckle and Sterling, 1996) was cited the most (29 citations) in 1996. The book highlights that EfS is a process in which the awareness and attitudes of individuals need to be developed to enable people to effectively develop a sustainable future and to make decisions that combine the social, cultural, economic and environmental aspects of living (Larkins et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…5.2.1 Teaching techniques used in engineering, management and other disciplines. Faculty members usually rely on textbooks to teach complex concepts like sustainability to fill the personal intellectual void of not being well versed with the concept (Larkins et al, 2018). A study of the readings assigned by US universities offering introductory sustainable courses by revealed "Green to Gold" and "Capitalism to Crossroads" as readings assigned at the undergraduate level and "Cradle to Cradle" and "Roadmap to Natural Capitalism" at the postgraduate level.…”
Section: Developments In Teaching Techniques/pedagogical Approachesmentioning
confidence: 99%
“…A study of the readings assigned by US universities offering introductory sustainable courses by revealed "Green to Gold" and "Capitalism to Crossroads" as readings assigned at the undergraduate level and "Cradle to Cradle" and "Roadmap to Natural Capitalism" at the postgraduate level. Larkins et al (2018) observed that only two textbooks contained references on public engagements. Bridges and Wilhelm (2008) suggested articles in journals featuring sustainable marketing practices, websites of known marketing magazines such as Fortune, Forbes and The Wall Street can compensate for the dearth of sustainability material in marketing.…”
Section: Developments In Teaching Techniques/pedagogical Approachesmentioning
confidence: 99%